Análisis sobre el perfil de directivos empresariales en México: caso de estudio (Analysis of the profile business executives in Mexico: case study) - Herrera, Emmanuel; Balderas Flores, Jorge A.; Chapa Cantú, Reynaldo (Facultad de Contaduría Pública y Administración U.A.N.L., 2012)
Abstract. A CEO, Managing Director or CEO as they call some companies in Mexico, have an important position within the organization and carrying out control of the human capital management companies, and acts as liaison between employees the company and senior management. For this research design was selected a quantitative study, this paper investigates the schooling of the CEO of the 300 best companies in Mexico for a total of 500 companies in Mexico in 2010. The CD (CEOs) have at least a bachelor's degree, master's and doctoral degrees. The specific level of education often depends on the nature of the business sector in which the company operates. CEOs of the 300 total, 273 have a Bachelor's representing 91% of the total, dominated by graduates of Business Administration with 44 cases represented by 15.88%. It was found that the average age between them is 54.1 years, age range is between 39 and 81 years, 149 of the 300 CEOs have a Masters degree accounting for 49.67%, of which 89 have Master Business Administration equivalent to 29.67%, 10 CD have the Ph.D. degree being 3.33%, of which a PhD in Business Administration ranks the 1.33% of the 4 cases that records the total population.